A stochastic approach to tumor modeling incorporating macrophages - Ucar, Sumeyra; Koca, İlknur; Özdemir, Necati; İnci, Tarık (Fırat Evirgen, 2024)
Macrophages are essential components of the immune system’s response to tumors, engaging in intricate interactions shaped by factors such as tumor type, progression, and the surrounding microenvironment. These dynamic relationships between macrophages and cancer cells have become a focal point of research, as scientists seek innovative ways to harness the immune system, including macrophages, for cancer immunotherapy. In this study, we introduce a novel model that examines the interaction between tumor and macrophage cells. We provide an in-depth analysis of the equilibrium points and their stability, as well as a thorough investigation into the solution properties of the model. Moreover, by incorporating a stochastic approach, we account for inherent randomness and fluctuations within the system, offering a more comprehensive understanding of tumor-immune dynamics. Numerical simulations further validate the model, providing key insights into how stochastic elements may influence tumor progression and immune response.
Keywords: Biological Mathematics; Biyolojik Matematik; Applied Mathematics (Other); Uygulamalı Matematik (Diğer)